EMPIRICAL STUDY OF THE FORMATION OF COMMUNICATIVE UNIVERSAL EDUCATIONAL ACTIONS IN YOUNGER STUDENTS - Solovyeva, Tatiana; Vitkovskaya, Irina; Ovchinnikova, Alexandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Effective pedagogical management of the formation of communicative skills in schoolchildren is impossible without monitoring the degree of their formation. The article presents the materials of diagnostic tools, including a questionnaire, criteria and nominative indicators for assessing the degree of formation of the components of communicative universal educational actions. The questionnaire is adapted to the age characteristics of younger students.On the basis of the developed criteria and indicators, a theoretical model of possible levels of mastery by younger students of the communicative actions of interaction, interiorization and cooperation is proposed. The article introduces the results of determining the levels of formation of communicative universal educational actions among elementary school graduates. The study was based on an analysis of literary sources, a survey of primary school students and theoretical modeling.